Density figures for urban restructuring? Adequate densities to safeguard the provision of public utilities in shrinking cities - Westphal, Christiane (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
Density is a key planning figure. It gains importance in shrinking cities. In Eastern German cities processes of shrinkage cause declines of urban densities with particular relevance for the provision of public utilities. Therefore, it is necessary to define spans of minimum densities from the perspective of public utilities for different urban structural types. Criteria to determine adequate densities for public utilities are compared against those deriving from other fields of planning such as transport, social facilities, green space provision and housing demand.